Enhanced photosynthesis, carbohydrates, and energy metabolism associated with chitosan‐induced drought tolerance in creeping bentgrass. Issue 2 (13th February 2020) - Liu, Zhaoqiao; Liu, Ting; Liang, Linlin; Li, Zhou; Hassan, Muhammad Jawad; Peng, Yan; Wang, Duo
Abstract: Chitosan (CTS) is involved in regulating tolerance to abiotic stress in plants. The objectives of this study were to examine whether exogenous application of CTS could improve drought tolerance of creeping bentgrass ( Agrostis stolonifera L.) and reveal CTS‐regulated mechanisms of drought tolerance. Antioxidant enzyme activities, photosynthesis, and metabolic pathways of amino acids, carbohydrates, and energy production were measured. Plants pretreated with or without 100 mg CTS L −1 were subjected to well‐watered or drought stress conditions for 14 d in growth chambers. The increase in endogenous CTS content by foliar spray of exogenous CTS significantly improved drought tolerance of creeping bentgrass as demonstrated by increased relative water content, cell membrane stability, photochemical efficiency, photosynthesis, and performance index on absorption basis under drought stress. The CTS application significantly reduced drought‐caused oxidative damage by enhancing total antioxidant capacity and activating superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase. During drought stress, pretreatment with CTS promoted water use efficiency, carbohydrate (sucrose and glucose) accumulation, energy production, and metabolic homeostasis. Chitosan treatment did not have an effect on proline accumulation and metabolism. Improved γ‐aminobutyric acid (GABA) accumulation, pyruvic acid, and chlorophyll content in leaves were found due to CTS treatment under drought stress. Results indicate that the CTS plays a positive role in regulating drought tolerance of creeping bentgrass by altering antioxidant, energy supply, and metabolic homeostasis.